Systematic comparison of InSAR and seismic source models for moderate-size earthquakes in Western China: implication to the seismogenic capacity of the shallow crust - Luo, Heng (2023)
Earthquake source parameters are important for understanding earthquake physics and crustal fault properties. However, strong trade-offs between parameters (e.g., depth and origin time) and a lack of accurate velocity models and near-field seismic stations could cause large uncertainties of these parameters in seismic catalogs, particularly for shallow events. To further improve the resolution of earthquake source parameters, we use Interferometric Synthetic Aperture Radar (InSAR) images to derive source solutions of 33 moderate-size (Mw 4.1–6.6) earthquakes that occurred at shallow depths (<20 km) from November 2014 to July 2020 in western China. After evaluating the uncertainties of the InSAR solutions, we systematically compare the location, centroid depth, focal mechanism and magnitude from InSAR models with that from seismic catalogs. We find that all seismic catalogs generally report deeper (4–10 km) hypocenters or centroid depths. The uncertainties of moment tensor solutions are partially related to the percentage of the non-double-couple components in the seismic catalogs. The InSAR solutions indicate that considerable seismic moments (i.e., ∼ (Formula presented.) Nm) were released in the uppermost crust (i.e., <5 km) in a period of ∼6 years, which is not resolvable in the seismic catalogs. The smooth seismic moment distribution along depth indicates a gradual change of the frictional properties from the surface to the middle crust. As most of the studied earthquakes are located on secondary and/or unmapped faults, these findings imply a considerable portion of velocity-weakening friction in the uppermost crust along immature, secondary fault systems, which should be included in the seismic hazard evaluation.